2022
DOI: 10.7557/19.6695
|View full text |Cite
|
Sign up to set email alerts
|

Dr. h.c. Johan Rooryck – an in-depth interview

Abstract: On 1 September 2022, professor of linguistics and director of cOAlition S Johan Rooryck was created a doctor honoris causa at UiT The Arctic University of Norway. In this in-depth interview, Rooryck reflects on his career so far and shares his vision of a future where scholar-led, fair and equitable open access prevails over commercial publishing structures. Johan Rooryck starts out by explaining how he became the editor-in-chief of the high-ranking journal Lingua in 1999, how his relations with the publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Auf funktionale Parallelen zwischen reduzierten Parenthesen und Satzadverbialen ist immer wieder hingewiesen worden. Rooryck (2001) Zur Motivierung, wenn auch nicht eigentlich prinzipiellen Herleitung, des ten Zusammenhangs sind zwei Sachverhalte interessant. Einmal Grammatikalisierungsprozesse, in deren Resultat satzförmige Parenthesen zunächst reduziert werden und dann weiter in einzelne lexikalische Elemente übergehen, zum anderen gewisse Fälle von Relativ-und Vergleichsätzen, bei denen ein Pronomen verstummen kann.…”
Section: Analogie Von Parenthese Und Sprechaktadverbialunclassified
“…Auf funktionale Parallelen zwischen reduzierten Parenthesen und Satzadverbialen ist immer wieder hingewiesen worden. Rooryck (2001) Zur Motivierung, wenn auch nicht eigentlich prinzipiellen Herleitung, des ten Zusammenhangs sind zwei Sachverhalte interessant. Einmal Grammatikalisierungsprozesse, in deren Resultat satzförmige Parenthesen zunächst reduziert werden und dann weiter in einzelne lexikalische Elemente übergehen, zum anderen gewisse Fälle von Relativ-und Vergleichsätzen, bei denen ein Pronomen verstummen kann.…”
Section: Analogie Von Parenthese Und Sprechaktadverbialunclassified
“…First, while deísmo and dequeísmo need not be coincident phenomena, the two have been related in the literature and feature an unselected particle de heading a subordinate sentence. Second, it has been proposed that some complementizers are indirect evidentiality markers (see Rooryck 2001): for example, that in English or van in Brabant Dutch (Van Craenenbroeck 2004); or certain uses of que in root sentences in Spanish Soriano 2014 andSánchez López 2020, among others). Given that in Section 2 we have shown that the particle de is a complementizer, it makes sense to ask whether it encodes evidential or modal values.…”
Section: The Meaning Of the Particle De 'Of'mentioning
confidence: 99%
“…According to Rooryck (2001), Aikhenvald (2018) and Sánchez López (2020), among the expressions (or grammatical strategies) that encode the source of information are complementizers. As we will see, at least that in English, van in Brabant Dutch and de in Spanish have been studied as complementizers encoding evidential values.…”
Section: Evidentiality and Variation In The Complementizer Phrasementioning
confidence: 99%
“…Interestingly, inferential interrogatives with qué show a behavior that is similar to inferential evidentials crosslinguistically. Bhadra (2018) analyzes the evidential marker naki in Bangla as a case of indirect evidence (Rooryck 2001) that can occur in different types of sentences, including interrogatives: (16) Sita baRi giy-ech-e naki? Sita home go-PERF-3SG NAKI 'Sita has gone home.…”
Section: Inferential Interrogatives With Qué Have a Confirmational Fl...mentioning
confidence: 99%